Distribution of corpora amylacea in the human midbrain: using synchrotron radiation phase-contrast microtomography, high-field magnetic resonance imaging, and histology - Lee, Ju Young; Mack, Andreas F.; Mattheus, Ulrich; Donato, Sandro; Longo, Renata; Tromba, Giuliana; Shiozawa, Thomas; Scheffler, Klaus; Hagberg, Gisela E. (Frontiers in Neuroscience, 2023)
Corpora amylacea (CA) are polyglucosan aggregated granules that accumulate in the human body throughout aging. In the cerebrum, CA have been found in proximity of ventricular walls, pial surfaces and blood vessels. However, studies showing their three-dimensional spatial distribution are sparse. In this study, volumetric images of four human brain stems were obtained with MRI and phase-contrast X-ray microtomography, followed up by Periodic acid Schiff stain for validation. CA appeared as hyperintense spheroid structures with diameters up to 30 µm. An automatic pipeline was developed to segment the CA, and the spatial distribution of over 200,000 individual corpora amylacea could be investigated. A threefold -or higher -density of CA was detected in the dorsomedial column of the periaqueductal gray (860-4200 CA count/mm 3 ) than in the superior colliculus (150-340 CA count/mm 3 ). We estimated that about 2% of the CA were located in the immediate vicinity of the vessels or in the peri-vascular space. While CA in the ependymal lining of the cerebral aqueduct was rare, the sub-pial tissue of the anterior and posterior midbrain contained several CA. In the sample with the highest CA density, quantitative maps obtained with MRI revealed high R2* values and a diamagnetic shift in a region which spatially coincided with the CA dense region.